Renal effect of severe hypoxia evaluated By NGAL measurements: An in vivo and in vitro study. Issue 1 (February 2022) - Sacco, Emilio; Vittori, Matteo; Ferraro, Pietro Manuel; Verde, Paola; Scagliusi, Alessandro; Baroni, Silvia; Masola, Valentina; Onisto, Maurizio; Nicosia, Maria; Bassi, PierFrancesco
Purpose: To investigate possible renal damage in healthy men exposed to extreme hypobaric hypoxia, using urinary Neutrophil Gelatinase-Associated Lipocalin (NGAL) concentration as biomarker. The value of NGAL as a biomarker of proximal tubular cell damage under hypoxic conditions was also tested in vitro experiments. Methods: NGAL was assayed in a cohort of air cadets ( n  = 16) exposed to hypobaric hypoxia in a hypobaric chamber during their training program. In all subjects, urine creatinine (Cr) and urinary NGAL levels were measured immediately before, 3, and 24 h after hypobaric environment exposure. Three in vitro experiments using proximal tubular cell cultures were also performed to measure NGAL gene expression, NGAL secretion in the culture medium and to evaluate apoptosis under two cycles of hypoxia and reoxygenation. Results: In the in vivo study, geometric means of urinary NGAL/Cr ratio measured 24 h after hypobaric hypoxia in the hypobaric chamber were significantly lower than baseline values (13.4 vs 25.9 ng/mg, p  = 0.01). In cell cultures, hypoxia down-regulated NGAL gene expression without significantly changing NGAL secretion in the culture medium. Hypoxia significantly increased the percentage of apoptotic/necrotic cells, especially after the second hypoxia-reoxygenation cycle. Conclusions: Exposure to hypobaric-hypoxic environments does not cause significant and irreversible renal tubular injury in vivo and in vitro, except than in a late stage. The hypoxic insult does not seem to be mirrored by an increase of urinary NGAL in healthy men nor of NGAL gene expression in HK-2 cell culture or secretion in the culture medium in the in vitro conditions reported in the present study.